Energy-efficient node selection in application-driven WSN - Marques, Bruno (2017)
The growth of wireless networks has resulted in part from requirements for connecting people and advances in radio technologies. Wireless sensor networks are an example of these networks in which a large number of tiny devices interacting with their environments may be inter-networked together and accessible through the Internet. As these devices may be scattered in an unplanned way, a routing protocol is needed. The RPL protocol is the IETF proposed standard protocol for IPv6-based multi-hop WSN. RPL requires that communication paths go through a central router which may provide suboptimal paths, not considering the characteristics of the applications the nodes run. In this paper is proposed an Application-Driven extension to RPL which enables to increase the WSN lifetime by limiting the routing and forwarding functions of the network mainly to nodes running the same application. As nodes may join a network at a non predictable time, they must be synchronized with respect to their application duty cycles. Therefore, nodes have to wake up and sleep in a synchronized way. In this paper it is also proposed such synchronization mechanism. The results confirm that the proposed solutions provide lower energy consumption and lower number of packets exchanged than the conventional RPL solution, while maintaining fairness and the packet reception ratio high.